An introduction to value-at-risk - Choudhry, Moorad (New York : Wiley, 2013)
The value-at-risk measurement methodology is a widely-used tool in financial market risk management. The fifth edition of Professor Moorad Choudhry's benchmark reference text An Introduction to Value-at-Risk offers an accessible and reader-friendly look at the concept of VaR and its different estimation methods, and is aimed specifically at newcomers to the market or those unfamiliar with modern risk management practices. The author capitalises on his experience in the financial markets to present this concise yet in-depth coverage of VaR, set in the context of risk management as a w.
Ratings changes over timeCorporate recovery rates; Credit derivatives; Measuring risk for a CDS contract; Modelling credit risk; Time horizon; Data inputs; CreditMetrics; Methodology; Time horizon; Calculating the credit VaR; CreditRisk+; Applications of credit VaR; Prioritising risk-reducing actions; Standard credit limit setting; Integrating the credit risk and market risk functions; 9 A REVIEW OF VALUE-AT-RISK; VaR in Crisis; Weaknesses Revealed; Market risk; Credit risk; Portfolio effects; New Regulation and Development; Procyclicality: stressed VaR (SVaR).
Keywords: Risk management; BUSINESS & ECONOMICS -- Insurance -- Risk Assessment & Management; Risk management; Electronic books